Activity of ventral hippocampal parvalbumin interneurons during anxiety - Emmanouela Volitaki; Thomas Forro; Kaizhen Li; Thomas Nevian; Stéphane Ciocchi (Cell Reports, 2024)
Summary: Anxiety plays a key role in guiding behavior in response to potential threats. Anxiety is mediated by the activation of pyramidal neurons in the ventral hippocampus (vH), whose activity is controlled by GABAergic inhibitory interneurons. However, how different vH interneurons might contribute to anxiety-related processes is unclear. Here, we investigate the role of vH parvalbumin (PV)-expressing interneurons while mice transition from safe to more anxiogenic compartments of the elevated plus maze (EPM). We find that vH PV interneurons increase their activity in anxiogenic EPM compartments concomitant with dynamic changes in inhibitory interactions between PV interneurons and pyramidal neurons. By optogenetically inhibiting PV interneurons, we induce an increase in the activity of vH pyramidal neurons and persistent anxiety. Collectively, our results suggest that vH inhibitory microcircuits may act as a trigger for enduring anxiety states.